Effect of hyperthermophilic pretreatment on methane and hydrogen production from garden waste under mesophilic and thermophilic conditions. (September 2021) - Liczbiński, Przemysław; Borowski, Sebastian
Graphical abstract: Highlights: two-stage anaerobic digestion of grass and leaves was studied. hyperthermophilic pretreatment significantly improved methane and hydrogen yield. several hyperthermophilic bacteria involved in lignocellulose degradation were found. hyperthermophilic Methanothermobacter could produce methane in the first stage. Abstract: Anaerobic digestion of garden waste was investigated in a two-stage process consisting of hyperthermophilic pretreatment followed by mesophilic or thermophilic fermentation. The greatest digestion performance was achieved when the substrates were first treated at 70 °C for 3 days with no inoculation, and then mixed with inoculum (anaerobic sludge) and subjected to anaerobic digestion at 55 °C. Under such conditions, the maximum methane and hydrogen yields from grass were 517 NmlCH4 /kgVS and 52 NmlH2 /kgVS, whereas the corresponding values for leaves were 421 NmlCH4 /kgVS and 23 NmlH2 /kgVS, and these figure were far greater than the yields obtained in experiments with no hyperthermophilic stage. A metagenomic analysis of hyperthermophilic environments revealed the appearance of thermophilic and hyperthermophilic bacteria showing hydrolytic activity against lignocellulosic materials, including Caldicellulosiruptor, Thermovenabulum, Thermoanaerobacter, Moorella, Tepimicrobium, Geobacillus and Thermobacillus at a genus level. A noticeable methane production in the hyperthermophilic stage could be linked to the presence of Methanothermobacter sp.